Bone mineral content and density among female NCAA Division I athletes across the competitive season and over a multi-year time frame - Stanforth, D.; Lu, T.; Stults-Kolehmainen, M. A.; Crim, B. N.; Stanforth, P. R. (The Journal of Strength and Conditioning Research, 2016)
Longitudinal and cross-sectional bone mineral content (BMC) and bone mineral density (BMD) comparisons were made among impact and nonimpact sports. Female collegiate athletes, 18-23 years of age, from basketball (BB; n = 38), soccer (SOC; n = 47), swimming (SW; n = 52), track sprinters and jumpers (TR; n = 49), and volleyball (VB; n = 26) had BMC/BMD measures preseason and postseason over 3 years. Control groups of 85 college females, 18-24 years of age, who completed 2 tests 1-3 years apart and of 170 college females, 18-20 years of age, were used for the longitudinal and cross-sectional analyses, respectively. A restricted maximum likelihood linear mixed model regression analysis with a compound symmetric heterogeneous variance-covariance matrix structure was used for all analyses (p = 0.05). Increases from year-1 preseason to year-3 postseason included the following: total BMC (3.3%), total BMD (1.4%), and spine BMD (4.5%) for BB; total BMC (1.5%) and leg BMD (1.2%) for SOC; arm (1.8%), leg (1.9%), and total BMD (5.7%) for SW; total BMC (2.0%), arm (1.7%), leg (2.3%), pelvis (3.4%), spine (6.0%), and total BMD (2.3%) for TR; and arm (4.1%), leg (2.0%), pelvis (2.0%), spine (2.0%), and total BMD (2.7%) for VB. Comparisons among sports determined that BB had higher BMC and BMD values than all other sports for all variables except spine and total BMD; BB, SOC, TR, and VB had higher total BMC (11-29%), leg BMD (13-20%), and total BMD (9-15%) than SW and CON, and there were few differences among SOC, TR, and VB. In conclusion, small, significant increases in many BMC and BMD measures occur during female athlete's collegiate careers. The BMC and BMD differences between impact and nonimpact sports are large compared with smaller differences within impact sports.